2006
DOI: 10.1037/0021-843x.115.3.524
|View full text |Cite
|
Sign up to set email alerts
|

Developmental trajectories of co-occurring depressive, eating, antisocial, and substance abuse problems in female adolescents.

Abstract: Growth trajectories of co-occurring symptomatology were examined in a community sample of 493 female adolescents who were followed annually from early to late adolescence. On average, depression, eating disorder, and substance abuse symptoms increased over time, whereas antisocial behavior decreased. Increases in each symptom domain were associated with relative increases in all other domains. Initial depressive and antisocial behavior symptoms predicted future increases in the other; substance abuse and antis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
156
3
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 182 publications
(178 citation statements)
references
References 101 publications
13
156
3
1
Order By: Relevance
“…These results seem to contradict other findings, suggesting that depressive symptoms in girls are predictive of a growth in eating pathology 14 and that there is an effect of chronic eating problems on depressive affect in subsequent years. 26 Nevertheless, when both types of problems coexist for adolescents, it could lead to subsequent academic, interpersonal, and behavioral problems.…”
Section: Resultscontrasting
confidence: 96%
See 2 more Smart Citations
“…These results seem to contradict other findings, suggesting that depressive symptoms in girls are predictive of a growth in eating pathology 14 and that there is an effect of chronic eating problems on depressive affect in subsequent years. 26 Nevertheless, when both types of problems coexist for adolescents, it could lead to subsequent academic, interpersonal, and behavioral problems.…”
Section: Resultscontrasting
confidence: 96%
“…10 As with other psychological problems, eating and depressive symptoms may covary as a function of shared risk or of a common underlying syndrome of psychopathology. 14 More longitudinal research is required to understand the developmental continuity of these problems in adulthood.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, using growth modeling, Edgerton and colleagues (2014) found that gambling problems tend to decrease over time in young adults (i.e., from ages 18 to 24 years). More studies have modeled changes in depressive symptoms across adolescence (Cole et al, 2002;Garber, Keiley, & Martin, 2002;Keenan, Feng, Hipwell, & Klostermann, 2009;Measelle, Stice, & Hogansen, 2006) and from adolescence to early adulthood (Galambos, Barker, & Krahn, 2006;Galambos, Leadbeater, & Barker, 2004;Ge, Lorenz, Conger, Elder, & Simons, 1994;Kim, Capaldi, & Stoolmiller, 2003). These studies have consistently found that levels of depressive symptoms are rather low during middle childhood but increase significantly over the course of early adolescence, albeit mainly in girls.…”
Section: Latent Trajectory Classes Of Problem Gamblers And-or Depressmentioning
confidence: 99%
“…15 These findings support the hypothesis that adolescents may smoke, consume alcohol, or use marijuana as a way to self-medicate and alleviate depressive symptoms. [15][16][17] Not every instance of witnessing violence results in adverse health outcomes, a difference that may depend on the availability of coping resources such as social support. For example, researchers conducted a longitudinal study and observed a lack of perceived social support to be a predictor for depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%